Kebiasaan Membaca Label Informasi Gizi dan Pengaruhnya terhadap Obesitas : Sebuah Literature Review - Salwa Alina Faza; Dian Isti Angraini; Sofyan Musyabiq Wijaya; Bayu Anggileo Pramesona (Medula, 2026)
Obesity is a growing global health problem, including in Indonesia. One preventative strategy is through the habit of reading nutritional information labels on packaged food products, which provide information on energy, fat, sugar, and sodium content. However, this habit remains low and has not been directly studied in relation to obesity incidence. This study is a literature review of articles from the Google Scholar, PubMed, ScienceDirect, and GARUDA databases from 2015–2025. Keywords used include "obesity," "nutrition information label," and "food label reading habits" in both Indonesian and English. The articles described are full-text and relevant to the topic. Several studies have found that individuals who regularly read labels tend to have a normal Body Mass Index (BMI). However, most of the literature only examines behavioral aspects or knowledge of nutrition labels, without exploring their direct link to obesity. Factors such as nutritional literacy, label design, and education significantly influence the effectiveness of labels on consumption. The habit of reading nutrition labels has the potential to help prevent obesity if accompanied by understanding and educational support. However, there is still a gap between knowledge and practice. A multidimensional approach is needed, including communicative label design, such as FoPNL, and ongoing regulation. Further studies are needed to examine the direct relationship between label reading behavior and obesity incidence.